Kebijakan Sektor Pertanian sebagai Awal Kebangkitan Ekonomi(Studi Kasus Taiwan Dalam Mengelola Komoditas Padi) - Kesa, Deni Danial; Lee, Cheng-Wen (Jurnal Vokasi Indonesia, 2013)
Indonesian agricultural has big potential to developed, but in fact most of our farmers are still many who are categorized as poor. Looking at Taiwan 's success in fostering innovation and empower agricultural resources , much can be learned in a production system . The policy implemented by the Ministry of agriculture and all stakeholders in Taiwan. For future prospects Indonesia, as applicable steps and future prospects, which should be applied in the rice production system in Indonesia such as maximizing the production of rice, with a maximum cost. Self-sufficiency for rice as staple food is main agenda for government , with expanding farmers rice fields in several potential areas and supported by the principle of conservation principles. Distribution of development agriculture particularly rice, should be offset consistent development of integrated technologies . Quantity must be short-term targets, with diversified land and production quality use unfettered access to farmers' access to protection in aspects of management, availability of equipment , andimpartial subsidies in accordance with applicable regulations . Policy implementation should be consistent with the applicable law and Indonesian agricultural development strategic plan together with all stakeholders.